(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Breast lesions are the leading cause of morbidity and mortality in women. Fine needle aspiration cytology (FNAC) ofBreast is a significant component of the “Triple approach” for pre-operative diagnosis of breast lumps. This study is undertaken to explorethe utility and accuracy of FNAC in various breast pathologies.Aim: This study aims to classify various breast lesions according to the International Academy of Cytology (IAC) grading system andgrade breast carcinoma on FNAC using Robinson's grading system which is then correlated with histopathology and also to evaluate thediagnostic accuracy, sensitivity, and specificity of FNAC in diagnosing breast lesions.Materials and methods: The study was conducted on patients with breast lump. This study was conducted by retrieving FNAC smears andwere grouped under five standardized categories proposed by the IAC: Category I (Insufficient material), Category II (Benign), CategoryIII (Atypical), Category IV (Suspicious) & Category V (Malignant) respectively. C5 cases were graded by Robinson's grading system whichwas then compared with the histopathological Elston Ellis modified Bloom-Richardson grading system.Results: Category I, II, III, IV, and V accounted for 10 (12.5%), 43 (53.75%), 3 (3.75%), 5 (6.25%), and 19 (23.75%) of the 80 breast lesionsreported on FNAC, respectively. Histopathology correlations were available in 59 cases. The sensitivity, specificity, positive and negativepredictive value, and diagnostic accuracy were 80%, 100%, 100%, 92.10%, and 94% respectively.Conclusion: Cytological characterization based on IAC structured reporting will enhance diagnostic clarity and comparison withhistopathology establishes the diagnostic accuracy of FNAC.